Functional restoration of exhausted CD4+ and CD8+ T cells in chronic viral infection by vinegar-processed flos of Daphne genkwa. (April 2015) - Uyangaa, Erdenebileg; Choi, Jin Young; Patil, Ajit Mahadev; Kim, Jin Hyoung; Kim, Seong Bum; Kim, Koanhoi; Ryu, Hyung Won; Oh, Sei-Ryang; Eo, Seong Kug
Abstract: T-cell exhaustion has become an important issue in chronic infection because exhausted antigen-specific T cells show impaired abilities to eradicate persistently infected pathogens and produce effector cytokines, such as IFN-γ and TNF-α. Thus, strategies to either restore endogenous exhausted T cell responses or provide functional T cells are needed for therapeutics of chronic infection. Despite promising developments using antibodies and cell immunotherapy, there have been no reported attempts to restore exhausted T cells using treatment with materials derived from natural resources. Here, using a mouse model of chronic infection with lymphocytic choriomeningitis virus (LCMV), we found that vinegar-processed flowers (flos) of Daphne genkwa (vp-genkwa), which was composed mainly of four index components, restored exhausted CD4 + and CD8 + T cells significantly, as corroborated by evidence that vp-genkwa treatment enhanced functional LCMV-specific CD4 + and CD8 + T cells, both quantitatively and qualitatively. Furthermore, pretreatment with vp-genkwa prevented the generation of exhausted LCMV-specific CD8 + T cells. Such restorations of exhausted LCMV-specific CD4 + and CD8 + T cells by vp-genkwa were closely associated with reduced viral burden in sera and tissues. More interestingly, vp-genkwa treatment induced down-regulation of negative molecules, such as PD-1 and Tim-3, in exhausted CD4 + and CD8 + T cells with more apparent down-regulation of Tim-3, suggesting that Tim-3 molecule may be a major target in restoring exhausted T cell responses. Collectively, these results provide valuable new insights into the use of vp-genkwa to develop a therapeutic strategy for chronic human diseases, such as hepatitis B and C virus, human immunodeficiency virus, and cancers.